Comparisons of outcomes after cordocentesis at mid-pregnancy between singleton and twin pregnancies - Srisupundit K. (2014)
Objective: To compare the outcomes after mid-pregnancy cordocentesis between singleton and twin pregnancies. Methods: We compared immediate complications and pregnancy outcomes between a cohort of twin pregnancies undergoing mid-pregnancy diagnostic cordocentesis between the years 1989 and 2010, and a control group of singleton pregnancies matched based on maternal age and years of the procedure with a ratio of 1:3. Results: Among 6147 pregnancies undergoing cordocentesis during the study period, 122 twin fetuses met the study criteria and were matched with 336 singleton controls. Success rate of sampling was slightly higher in singleton than in twin gestations (98.8% vs 97.3%), and time required for the procedure was significantly longer in the twin group (8.1 vs 6.3 min, p = 0.02). Immediate complications, such as fetal bradycardia and transient bleeding from the puncture site, were significantly higher in twins (13% vs 6.0%, p = 0.001; and 34.8% vs 26.1%, p = 0.03, respectively). However, fetal loss rate within 2 weeks of cordocentesis was not different (1.4% and 1.1%, p = 0.42). Conclusion: Immediate complications following cordocentesis are significantly higher in twin pregnancies, but fetal loss rate within 2 weeks of the procedure is comparable. © 2011 John Wiley & Sons, Ltd.